Analisis Kota Yogyakarta Sebagai Kota kreatif: Pendekatan Sinergitas Quadro Helix - Prayudi Prayudi; Kartika Ayu Ardhanariswari; Ninik Probosari (Eksos LPPM, 2020)
The purpose of this study is to analyse the development of Yogyakarta as creative city. The analysis was done based on the quadro helix model approach. Building the concept of quadro helix with producing creativity and innovation capability requires the participation of four sectors, namely government, academician, entrepreneur, and society. This framework emphasizes a societal responsibility of universities, in addition to their role of educating and conduction research. The quadruple helix model has been argued to include both the civil society and the users of innovation. Therefore, it requires an approach that combines the synergy between academicians, entrepreneurs, government, and society in aquadro helix model. The objective of this research is to develop a creativity model through a quadro helix model in improving innovation performance ofthe creative cities. Creative cities based on local potentials as regional excellence and identity need to be encouraged to increase added value and competitiveness, and be able to become the centre of growth for the surrounding area. Based on this background, an understanding of how the concept of creative city is applied in Indonesia's creative city is interesting to look at. In this research, the analysis was focused on Daerah Istimewa Yogyakarta that was as a creative city. This study used qualitative research method. This method systematically describes the facts or characteristics of a particular population or a particular field factually and accurately. Particularly, in-depth interview and focus group discussion were conductedto obtain detailed information from government, academics, and community groups. Findings of research indicate some challenges in the development of Yogyakarta as creative city. First was to identify the economic potentials of the city. Second was the existence of creative class within community. Third was the existence of supporting environment for the creativity of community to grow. Of these three challenges, the government of the City of Yogyakarta was slow in providing relevant infrastructures.